Novel Chlorin with a HYNIC: Synthesis, 99mTc-Radiolabeling, and Initial Preclinical Evaluation - Alexander Popov; Nikita Suvorov; Mariia Larkina; Evgenii Plotnikov; Ruslan Varvashenya; Vitalina Bodenko; Gleb Yanovich; Petr Ostroverkhov; Maxim Usachev; Elena Filonenko; Mikhail Belousov; Mikhail Grin (Molecules)
The use of radiopharmaceuticals for diagnostics in oncology allows for the detection of the disease at an early stage. Among diagnostic radionuclides, 99mTc is a promising isotope that has been used to create several drugs for clinical use. One of the most effective 99mTc chelators is 6-hydrazinylnicotinic acid (HYNIC), which, when combined with various vector molecules, can be used for targeted delivery of radionuclides to tumor tissues. At the same time, it is known that tetrapyrrole macrocycles are capable of selective accumulation in tumors, and thus can be used to target radiopharmaceuticals with 99mTc. In this work, the conjugate of natural chlorin and HYNIC was obtained, and preliminary preclinical studies were carried out on its radiocomplex with 99mTc.